Exploring the Role of TPACK in Promoting Inquiry-based Learning in 21 - Teknowijoyo, Felixtian; ., Gunarhadi; ., Budiyono; ., Sukarmin (KnE Social Sciences, 2024)
The realm of science education is grappling with the growing demand to equip learners with the scientific reasoning and technological capabilities vital for the 21st century. In light of this, the present study delves into how Technological Pedagogical Content Knowledge (TPACK) can enhance inquiry-driven approaches in modern-day science education. Using a literature review as its methodological approach, this research ascertains that TPACK is pivotal in making inquiry-based learning more accessible in science pedagogy. Specifically, educators who possess a profound grasp of TPACK can seamlessly weave technology into science lessons, tailor their teaching methods to cater to student requirements, and combine scientific factual knowledge with analytical reasoning abilities. As it pertains to applying an inquiry-driven curriculum, TPACK empowers educators to design engaging, collaborative, and experiential learning scenarios within the ambit of scientific exploration. Consequently, this study sheds light on the instrumental role of TPACK in science education of the 21st century, advocating for a more dynamic and learner-focused approach. This research underscores the need for specialized training and continual professional enhancement with a spotlight on cultivating TPACK skills among science educators. Furthermore, the insights derived from this study can pave the way for avant-garde curriculum frameworks and pedagogical structures, further championing inquiry-oriented instruction in contemporary science education. Keywords: TPACK, science education, inquiry based learning, 21st century